Exploring the influence of target atomic number (Z2) on mean equilibrium charge state (q¯: A comprehensive study - Swami, D. K.; Kumar, Sarvesh; Singh, Balwinder; Karn, R. K. (Frontiers in Physics, 2023)
We have investigated the effect of the target atomic number Z_2 on mean charge state (q ̅) using various model predictions such as Shima-Ishihara-Mikumo, Ziegler-Biersack-Littmark, Schiwietz Model, Schiwietz-Grande model, Fermi-gas-model and theoretical codes with experimental data available in the literature. This investigation makes it possible to determine the best fit model to calculate q ̅. In this work, we discuss the post-collision charge state distribution in different targets used as thin films and projectile beams (Fq+, Siq+, Clq+, and Cuq+) with different charge states (Available in Literature). A detailed overview of such collision experiments has been explored in a wide energy range of 1.07 - 3.93 MeV/u. In this contribution, an overview of the mean charge state dependence on the Fermi velocity of target materials is provided. Finally, the influence of the non-radiative electron capture at the target exit surface on the projectile charge state distribution for fast projectiles in different targets is shown and a comparison is made with experimental data.